Awareness of Consumer Rights on Marketing Practices in Kailali District of Nepal - Rawal, Dhavindra (Far Western Review, 2023)
The aim of this study is to examine the awareness status of consumer rights on marketing practices in Kailali district of Nepal. The empirical study depends on a convenience sample of 418 consumers in different locations of Kailali district with a structured questionnaire to measure consumer awareness regarding four consumer rights: Right to safety, right to be informed, right to choose and right to be heard, utilizing a five-point Likert scale for measurement. The overall findings show that the current consumers’ awareness towards marketing practices related to protection of consumer rights is medium favorable. There is significant difference among the gender, age group, occupation and educational level except location of the consumers related to the consumer awareness. In addition, consumer awareness leads to a rational buying behavior, critical thinking, right decision to purchase, improved life skills, increased self-confidence and safe from market exploitations. The outcomes of the study become important to consumers, consumer forum, business firms, government units and policy makers for understanding the current status of consumer rights with implications for better business practices issuing on policy making for consumer protection.